Indonesia Military Research and Development in Dealing with the Sixth Generation Warfare: The Use of Artificial Intelligence in War Operations - Irvan Arianto Randa Lembang; Romie Oktavianus Bura; R Djoko Andreas Navalino; Lutfi Adin Affandi (Jurnal Multidisiplin Madani, 2023)
Technological advancement has forced the international community to deal with the sixth generation of war, which is a conflict involving the most advanced robotics, artificial intelligence (AI), and satellite technology. This shows that warfare has evolved beyond traditional tactics because parties are no longer required to engage in face-to-face combat as they did during the first generation of conflicts. Although the "classic" war still takes place in some regions of the world, it is more sectoral in nature and only in small-scale wars. The researcher needed a description of Indonesian military research and development in dealing with sixth generation warfare: the application of artificial intelligence in military operations, hence the qualitative descriptive research approach was used. The Indonesian National Armed Forces (TNI) must be flexible in light of the dynamics of the world's swift technology advancements, which includes updating defense equipment with artificial intelligence (AI) functionality. Due to increasingly sophisticated danger patterns, the TNI must deploy artificial intelligence, making technological advancements crucial to safeguarding the security of border areas. Keeping the Republic of Indonesia's unitary state intact comes with a "fixed price," one of which is preserving the security of the border region